An innovation systems approach to capacity development: Insights from learning exercises with the Feed the Future Innovation Lab for Livestock Systems in Ethiopia - Ye, Jia Yi; De Roo, Nina; Spielman, David J. (International Food Policy Research Institute, 2019)
This report details the project’s engagement with the FTF Innovation Lab for Livestock Systems, led by UFL, and its Livestock Innovation Platform in Ethiopia, led by the International Livestock Research Institute (ILRI). The engagement—framed here as a case study in systems-oriented capacity development—was conducted in 2019, and included a series of multistakeholder learning events held in Addis Ababa, Ethiopia in late August 2019.